Consequences of fish farming cessation on carrying capacity for ducks breeding on French fishponds - Broyer, Joël; Curtet, Laurence; Chavas, Gilles (Wildfowl, 2021)
The demise of fish farming is one of several hypotheses proposed to explain the decline of Common Pochard Aythya ferina (hereafter Pochard) in Europe. Here we study habitat changes at Pochard breeding sites in Forez, central-eastern France, where traditional fish farming has been abandoned at many ponds since the 1990s. We compared variation in water and sediment physicochemical characteristics in ponds stocked with Common Carp Cyprinus carpio, versus ponds abandoned by fish farmers for ≥ 5 years, during early April to July 2016, as well as contrasting development of phytoplankton (measured as chlorophyll a), macrophytes, duck pair density and the brood:pair ratio. Carp stocking (biomass density usually ≥ 200 kg/ha) was associated with elevated June phosphate (PO4) pond water concentrations and with a decreased nitrogen loading, while PO4 and nitrogen levels remained stable in abandoned ponds throughout the study period. Carp stocking was also linked to lower phytoplankton density (chlorophyll a) in June and higher macrophyte cover, together with higher diving duck pair density and a higher duck brood:pair ratio. Such results suggest that bioturbation of pond sediment by foraging carp may favour macrophyte development by mobilising sediment phosphorus into pond water, thereby improving primary productivity of the aquatic ecosystem, and thus habitat conditions for ducks breeding at these sites.